Effect of Leisure Activity Participation on Leisure Attitude, Recreational Specialization, Leisure Satisfaction, and Intention to Re-Participate in South Korea - Byoungwook Ahn (Behavioral Sciences)
The importance of leisure in post-COVID-19 society has been underscored by the pandemic, illustrating the need to view leisure not merely as an option but as an essential component of a fulfilling life. This study investigates whether leisure attitudes, considered a novel perspective or belief regarding leisure, along with leisure activities, recreational specialization (the process of becoming proficient in particular leisure activities), and satisfaction derived from these experiences, prompt continued participation. The study surveyed 259 adults, both men and women, residing in Seoul, Gyeonggi, and Chungcheong Province who had engaged in leisure activities for over a year. Data were analyzed using the SPSS 21 program for frequency, reliability, and correlation analyses, while confirmatory factor analysis and structural equation modeling were performed with the AMOS 18.0 program. The research yielded the following findings: Firstly, the leisure attitudes of participants significantly influenced their leisure satisfaction. Secondly, their leisure attitudes did not influence recreational specialization. Thirdly, their attitudes did not affect their intention to re-participate. Fourthly, recreational specialization significantly affected both leisure satisfaction and intention to re-participate. Lastly, leisure satisfaction significantly influenced the intention to re-participate. With the evolving perceptions of leisure post-pandemic, there is a need for policies and infrastructure that support the sustainable engagement of leisure activity participants.